Collisional line broadening and mixing in the Raman spectrum of CO perturbed by N2: Experimental measurements and theoretical calculations. (November 2021) - Paredes-Roibás, Denís; Martínez, Raúl Z.; Jóźwiak, Hubert; Thibault, Franck
Highlights: Joint theoretical and experimental lineshape study in the rovibrational isotropic Raman spectrum of CO in a bath of N2 between 77 and 298 K. Determination of collisional broadening coefficients. Determination of line mixing coefficients. Comparison of experimental vs.theoretical results and evaluation of the effect of the different approximations used in the calculations Graphical abstract: Abstract: We present a joint experimental and theoretical study of line broadening and mixing in the Q branch of the Raman spectrum of CO perturbed by N2 at 77, 195 and 298 K. Advanced methods and facilities have been used for both aspects of the study: the experiments were conducted using a high-resolution stimulated Raman spectroscopy setup, while the calculations were performed using a quantum dynamical formalism and one of the most recent potential energy surfaces available. Line broadening coefficients were determined experimentally for rovibrational lines up to j = 11 at 77 K, j = 15 at 195 K and j = 19 at 298 K, and calculated for lines up to j = 6 at the three temperatures. Line mixing was also observed and coefficients measured for lines up to j = 8 at 77 K and j = 5 at 195 K, and again calculated up to j = 6 at the three temperatures. A comparison shows an overall very good agreement between experiments and calculations for both sets of coefficients. Additional calculated data for the pure rotational R and S lines are also provided.